\root(3)(-3)\root(3)(-5)=\root(3)(15) true or false
![root33root35root315 true or false class=](https://us-static.z-dn.net/files/de0/504e723b145150a259370ef64da633b7.gif)
The equation [tex]\sqrt[3]{-3} \cdot \sqrt[3]{-5} = \sqrt[3]{15}[/tex] is true
The equation is given as
[tex]\sqrt[3]{-3} \cdot \sqrt[3]{-5} = \sqrt[3]{15}[/tex]
Apply the law of indices
[tex]\sqrt[3]{-3 * -5} = \sqrt[3]{15}[/tex]
Evaluate the product
[tex]\sqrt[3]{15} = \sqrt[3]{15}[/tex]
Both sides of the equation are the same
Hence, the equation [tex]\sqrt[3]{-3} \cdot \sqrt[3]{-5} = \sqrt[3]{15}[/tex] is true
Read more about equations at:
https://brainly.com/question/2972832
#SPJ1